A novel design of smart knee joint prosthesis for above-knee amputees - Kamel Shaimaa H.; Hamzah Mohsin N.; Abdulateef Saad A.; Atiyah Qasim A. (FME Transactions, 2023)
Amputees suffer greatly from lower limb amputation. A novel smart knee joint prosthesis was constructed in this research to allow the amputee to achieve regular daily movement, such as walking, standing, and ascending/descending stairs. This prosthesis employs sensors, actuators, and a mechanical system to replicate the functioning of a natural limb. As a result of the unique mechanical and electrical components employed herein to boost performance, metabolic energy is lowered. Here, a ball screw is employed, which has been determined to be the most efficient means of achieving linear motion; its precision and efficiency range from 90% to 100%. It is quieter and more efficient than a hydraulic or pneumatic system. An electromechanical linear actuator (servo cylinder) is used with an actuator control system and integrated Phase Index - Field-Oriented Control. It maintains and self-calibrates the needed position with high precision when power or backup power is unavailable. The angle of flexion achieved in this design is 120º. The gait analysis revealed that the current prosthesis could imitate the biomechanics of the normal joint with no difficulty at varied speeds when tested on an amputee (110 kg). Furthermore, it may function efficiently as a passive when power is unavailable, including the capacity to move smoothly throughout the swing phase (high accuracy through deceleration and acceleration). The current active knee joint is lightweight (2869 grams), and the cost has been greatly reduced.